2022
DOI: 10.4236/ajibm.2022.1212098
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Issue and Strategic Importance of Its Solution in the Republic of Armenia

Abstract: The article presents the study results related to the disclosure of food safety issues in the Republic of Armenia and to the strategic importance of their solution. Taking into account the utmost strategic importance of solving the food security issue, it is necessary to handle the following key problems: 1) ensuring sustainable and balanced development of the agro-industrial complex and its individual branches (plant growing, animal husbandry, material and technical maintenance and services, agricultural raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The "Anush" variety bred in the scientific center has served as a control variant for the new variety. The results of ecological trials of the mentioned varieties have shown, that in both climatic conditions the mentioned varieties have ensured high yielding capacity [12].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The "Anush" variety bred in the scientific center has served as a control variant for the new variety. The results of ecological trials of the mentioned varieties have shown, that in both climatic conditions the mentioned varieties have ensured high yielding capacity [12].…”
Section: Resultsmentioning
confidence: 94%
“…The goal of the research group was to get super early ripening groundnit varieties via expanding the sown areas of the mentioned crop. In the result high-yielding early-season variety "Lia" has been obtained and regionalized which together with "Arina" variety, currently under state variety testing, has been subjected to ecological testing in conditions of piedmont zone of the republic [11,19].…”
Section: Methodsmentioning
confidence: 99%
“…In 2022, it amounted to 1366.6 million US dollars, or 15.59% of total imports, per the data. 8.98% of them were agricultural products [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to certain types of agricultural products of strategic importance, this situation may adversely affect the country's food security, since the level of self-sufficiency in these products is noticeably low. In particular, in 2021, the level of self-sufficiency in wheat was 23.2%, pork meat -53.2%, poultry meat -26.7% (Ghukasyan et al 2022; https://www.armstat.am/am/?nid=81).…”
Section: Introductionmentioning
confidence: 99%